2009
DOI: 10.1007/s00259-009-1313-8
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid scintigraphy findings in chronic kidney disease patients with recurrent hyperparathyroidism

Abstract: Many patients referred with the hypothesis of hyperplasia of a subtotally resected parathyroid gland or autograft were found to harbour a supernumerary parathyroid gland missed at the initial surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 69 publications
0
41
1
Order By: Relevance
“…Most investigators thought that there was an inability in detection of especially small glands [1,3,13]. A wide range of sensitivity values (28-88%) was reported for the planar scanning and this condition was found to be related to the above-mentioned false results [1][2][3][4][5]11,12,[14][15][16]. The sensitivity (36%) was also lower for planar scans in our series.…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…Most investigators thought that there was an inability in detection of especially small glands [1,3,13]. A wide range of sensitivity values (28-88%) was reported for the planar scanning and this condition was found to be related to the above-mentioned false results [1][2][3][4][5]11,12,[14][15][16]. The sensitivity (36%) was also lower for planar scans in our series.…”
Section: Discussioncontrasting
confidence: 48%
“…Planar and SPECT scans for patients with sHPT had lower sensitivity rates. SPECT imaging with the double-agent subtraction method has been found to be useful partly for reoperated cases or for concomitant thyroid nodules [1,4,14]. Currently, a limited number of studies have reported that better results can be obtained with pSPECT [13,16,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…99m Tc-sestamibi, a lipophilic cation of the isonitrile family is accumulated and retained in the mitochondria of oxophil-rich parathyroid adenomas. 99m Tc-sestamibi has been used to perform parathyroid scintigraphy in conjuction with 99m Tc-pertechnetate or 123 I for thyroid tissue subtraction (50). In 1992, Taillefer introduced a dualphase protocol with 99m Tc-sestamibi alone, to exploit its differential kinetic properties in thyroid and parathyroid tissues.…”
Section: E Radioisotopes Commonly Used For Investigation Of Endocrinmentioning
confidence: 99%
“…Some authors have reported very high percentages of supernumerary parathyroid glands in patients with renal failure and persistent HPT (Hindié et al, 2010;Uno et al, 2008). However, persistent disease is defined and accepted by the authors as the reappearance of typical symptoms, laboratory abnormalities and radiological signs within six months of PTS (Hindié et al, 2010).…”
Section: Discussionmentioning
confidence: 96%